Parental attitude, depression, anxiety in mothers, family functioning and breath‐holding spells: A case control study. (18th April 2016) - Eliacik, Kayi; Bolat, Nurullah; Kanik, Ali; Sargin, Enis; Selkie, Ellen; Korkmaz, Nurhan; Baydan, Figen; Akar, Ebru; Sarioglu, Berrak
Abstract : Aim: This study aimed to identify differences in the antenatal stressful life events, parenting style, family functioning, depression and anxiety of mothers who have children with breath‐holding spells (BHS) compared with controls. Methods: This case control study divided 66 children into a group of children with BHS and a control group, with the children's ages ranging between 6 months and 5 years of age. This study explored underlying anxiety and depression in mothers as well as functioning of their families. Socio‐demographical data and stressful life events that the mother experienced during pregnancy were analysed. In order to evaluate the effects of family structure, depression and anxiety in mothers on BHS in children, the Family Assessment Device, and both the Parental Attitude Research Instrument and the Beck Depression Inventory as well as the State‐Trait Anxiety Inventory were used to assess both groups. Results: Exposure to stressful life events during pregnancy ( P  < 0.001), depressive traits ( P  < 0.001), state‐trait anxiety ( P  < 0.001), overprotective maternal characteristics ( P  = 0.027) and most of the family functioning subscales were found to be significantly different between BHS and control groups. Conclusions: The association of anxiety, depression, prenatal stressful events and poor family functioning in mothers who have children with BHS is significantly higher than controls. An evaluation of these problems may be beneficial in the management of BHS.